Gold(i)-catalysed cascade reactions in the synthesis of 2, 3-fused indole derivatives1. Issue 62 (11th August 2015) - Gimeno, Ana; Rodríguez-Gimeno, Alejandra; Cuenca, Ana B.; Ramírez de Arellano, Carmen; Medio-Simón, Mercedes; Asensio, Gregorio
<x xml:space="preserve">Abstract</x> Unactivated alkenes and 1, 3-unsubstituted indoles in gold(i)-catalysed hydroaminative/arylative cascade cyclizations.